Cytokine Expression by Human Macrophage-Like Cells Derived from the Monocytic Cell Line THP-1 Differs between Treatment with Milk from Preterm- and Term-Delivering Mothers and Pasteurized Donor Milk - Veronique Demers-Mathieu; Robert K. Huston; David C. Dallas (Molecules, 2020)
Immunomodulatory proteins from human milk may enhance the protection and development of the infant’s gut. This study compared the immunomodulatory effects of treatment with milk from preterm-(PM) and term-delivering (TM) mothers and pasteurized donor milk (DM) on cytokine gene expression in human macrophage-like cells derived from the monocytic cell line THP-1. The gene expression of tumor necrosis factor-α (TNF-α), interleukin (IL)-6, IL-12 (p40), IL-10 and GAPDH in macrophages treated with PM, TM and DM at steady and activated (inflammatory) states were measured using real-time reverse transcription-polymerase chain reaction. TNF-α and IL-6 in macrophages (both states) with DM were higher than PM or TM. IL-10 in steady state macrophages with DM was higher than PM whereas DM increased IL-10 in activated macrophages compared with TM. TM increased IL-6 and IL-12 (p40) in steady state macrophages compared with PM. IL-12 (p40) in activated macrophages with TM was higher than PM. IL-10 in steady state macrophages with TM was higher than PM. These results suggest that DM induces higher gene expression of pro-inflammatory and anti-inflammatory cytokines in macrophages compared with PM or TM. PM reduced gene expression of pro-inflammatory cytokines compared with TM, which may decrease the development of necrotizing enterocolitis and systematic inflammation.